Measuring fiscal sustainability on the municipal level: A German case study - Christian Hagist; Johannes Vatter (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2009)
The consequences of ageing populations for federal and state fiscal policies are, due to the research efforts of the last two decades, well known. However, it is rather less well known how the municipal level is affected. Therefore, by using a modification of the sustainability definition formulated by Blanchard, Chouraqui, Hagemann, and Sartor (1990) and the concepts of Auerbachs, Kotlikoffs and Gokhales Generational Accounting (1991) we define a new framework focusing on capital stock, financial management and depreciation of municipal assets. This papers purpose is to deliver a concept which is able to provide sound indicators for long-term budgeting by local authorities. We apply this framework to three German cities with different typologies, Munich, Freiburg and Schwäbisch Hall.
Keywords: 330; Fiscal sustainability; demographic transition; municipalities; Gemeindefinanzen; Nachhaltigkeit; Alternde Bevölkerung; München; Freiburg (Breisgau); Schwäbisch Hall